Internationalizing higher education in Korea challenges and opportunities in comparative perspective - O, Yaeon-ch'aeon; Shin, Gi-Wook; Moon, Rennie (Walter H. Shorenstein Asia-Pacific Research Center Freeman Spogli Institute for International Studies, 2016)
"Student mobility to and among higher education systems in Asia has reached unprecedented levels. In particular, inbound and outbound student mobility creates twin challenges-growing diversity in host countries and brain drain and circulation for sending countries-that have significant implications for growing intra-regional mobility, competition, and cooperation within Northeast Asia. This book examines these and other related, timely issues for the case of South Korea, a major player in the internationalization of higher education in Asia, and draws on the experiences of other key players in the region and beyond-Japan, China, Singapore, and the United States-to engage in a comparative discussion of Korea's successes, failures, and ongoing challenges. By doing so, Internationalizing Higher Education in Korea offers critical perspectives on the internationalization of Korean higher education as well as innovative, policy-relevant solutions for Asian countries undergoing similar challenges. It will be a valuable addition to the growing literature on comparative and international education in Asia and can aid university administrators and policymakers striving to internationalize their higher education systems to meet new challenges"--Provided by publisher.